Motif di Balik Bantuan Jepang untuk Palestina dalam Kerangka CEAPAD - Ryantori, Ryantori (Jurnal Hubungan Internasional, 2014)
This paper discusses the main motives behind Japanâs foreign aid to Palestine. It is likely that Japan starts to play its role as foreign aid broker. Recently, this country has been inviting other countries, especially in East Asia, to be involved in its foreign aid programs. CEAPAD (Conference on Cooperation among East Asian Countries for Palestinian Development )is the example to be mentioned. This is the first time East Asia countries talk together to support Palestine in order to be able to manage foreign aid efficiently. Surprisingly, although this conference used East Asia as its tagline, six of ten ASEAN members (Brunei, Indonesia, Malaysia, Thailand, Singapura, Vietnam) attended this conference but China as major state in East Asia region did not. At one side, it seems that Japan is trying to get good image from Asian countries in order to challenge the increasing image China has got so far. At the other side, potential market in Arab and Palestine region as well as in Asiaâespecially East and Southeast Asiaâ are still in grasp. Whether political or economic motives which drives Japan to put CEAPAD into surfaces, Palestinian Authority and people has had huge expectations from this.